RECOVERY OF MORE THAN 10 YEARS-DRYING Monascus CULTURES AND ITS PURIFICATION METHODS FROM FUNGAL AND BACTERIAL CONTAMINATION - Nandang Suharna (BIOTROPIA, 2008)
This study was carried out to understand the recovery capability of more than 10 years- drying Monascus cultures. A new simple purification technique from fungal contamination using ethanol-soaking treatment was also reported as a part of this study. The result showed that all drying cultures were recovered well and retained their characters such as good growth, pigmenÂtation and production of fruit bodies (ascomata), sexual spores (ascospores) and asexual spores. Several cultures showed its good growth in 20% ethanol medium. This study also reported sucÂcessful purification of cultures from fungal contamination using ethanol-soaking treatment. This self-drying method, therefore, could be suggested as a good long-term preservation method for Monascus cultures. Moreover, purification method from fungal contamination soaked in ethanol 70% or 95% was successfully effective.